The evaluation of transit transport probable effects on the development of country’s economy - Litvinenko, Michail; Palšaitis, Ramūnas (Transport, 2006)
The article describes the peculiarities of transit transport influence on the development of country’s economy. The authors analyze transit transport definition and define the economic importance of transit transport. The first part of the article is assigned to the consideration of transit cargo transportation as an integral object of scientific research. The survey is supported with the comparative analysis of different scientists’ approaches to the transit transportation performance modelling. The evaluation of transit transport benefit for the economy of the country is presented. The concise summary of a principal thesis and conclusions may be useful for further analyses of different aspects or transit transport. First Published Online: 27 Oct 2010